Physiology of menopause and the role of hormone therapy - Sabyasachi Moulik (Advances in Physiology Education, 2026)
Natural menopause, a biological transition in women, is often underrepresented in medical education, leading to knowledge gaps among healthcare professionals. This Staying Current article aims to provide physiology educators with an updated, comprehensive overview of menopause, including its physiological basis, symptomatic manifestations, systemic effects, and the current controversies and benefits surrounding menopausal hormone therapy (MHT). This article details the hormonal regulation of reproductive aging, the STRAW and STRAW+10 criteria for characterization of menopausal staging, and the pathophysiology of common menopausal symptoms such as vasomotor disturbances, genitourinary syndrome, mood and sleep disturbances. It critically examines the history, risks, and benefits of MHT, referencing pivotal studies like the Women’s Health Initiative, and outlines non-hormonal management strategies. Addressing educational gaps in menopause physiology is essential for improving women’s health outcomes. This article equips physiology educators with current evidence and recommendations to enhance curricula and patient-centered care.